Prevalence of tuberculous lymphadenitis in Gondar University Hospital, Northwest Ethiopia - Muluye, Dagnachew; Biadgo, Belete; Woldegerima, Eden; Ambachew, Andebet (BMC public health, 2013)
Background Tuberculous is the leading cause of death worldwide with a large number ofdeaths occurring in developing countries. Tuberculous lymphadenitis is amongthe most common presentations of extra pulmonary tuberculous. This studyattempts to determine the magnitude of tuberculous lymphadenitis frompatients with lymph node aspirate in Gondar University Hospital, NorthwestEthiopia. Methods Retrospective study was conducted. Data were collected from registration bookof Gondar university Hospital pathology laboratory after checking thecompleteness of patient’s necessary information like age, sex and fineneedle aspiration cytology results. Data were entered and analyzed usingSPSS version 16 statistical package. Chi-square test was done to determineassociations. Result A total of 3,440 lymph node aspirates were examined using fine needleaspiration cytology. Of these, 2,392 (69.5%) cases were found to havetuberculous lymphadenitis. Male 1647(47.9%) to female 1793(52.1%) ratio ofall study subjects were 0.9:1. Females (54.1%) were more affected than males(45.9%). Age, sex and site of aspiration were found to be statisticallyassociated with tuberculous lymphadenitis (p-value < 0.001).The age group of 15–24 years had the highest prevalence of tuberculouslymphadenitis followed by those of 25–34 years old. The most affectedsites were cervical lymph nodes (47.5%) followed by auxiliary (19.4%) andsubmandibular (12.9%) lymph node regions. None of the records documented theHIV status of subjects. Conclusion The prevalence of tuberculous from lymph node aspirate was found to be higherinvolving the frequently affected site of cervical lymph node. The HIVstatus of patients with all forms of tuberculous should have to be checkedand documented. Further prospective and advanced studies are recommended todetermine the specific etiologic agents and contributing factors.